2017
DOI: 10.1186/s12885-017-3386-2
|View full text |Cite
|
Sign up to set email alerts
|

ICORG 10-14: NEOadjuvant trial in Adenocarcinoma of the oEsophagus and oesophagoGastric junction International Study (Neo-AEGIS)

Abstract: BackgroundNeoadjuvant therapy is increasingly the standard of care in the management of locally advanced adenocarcinoma of the oesophagus and junction (AEG). In randomised controlled trials (RCTs), the MAGIC regimen of pre- and postoperative chemotherapy, and the CROSS regimen of preoperative chemotherapy combined with radiation, were superior to surgery only in RCTs that included AEG but were not powered on this cohort. No completed RCT has directly compared neoadjuvant or perioperative chemotherapy and neoad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 31 publications
0
115
1
1
Order By: Relevance
“…Trimodality therapy for esophageal and esophago-gastric cancer combining neoadjuvant chemo-and radiation-therapy in addition to surgery may also be superior to neoadjuvant chemotherapy alone in a selected patient population [8]. The CROSS trial [6] comparing neoadjuvant chemoradiotherapy plus surgery with surgery alone in patients with esophageal and esophago-gastric cancer showed a superior overall-survival of 49 vs. 24 months, hazard ratio 0.657, p = 0.003, and a pathological complete response rate of 29%, for patients with multi-modality treatment with no increase in surgical mortality (4% in surgery and trimodality groups, respectively).…”
Section: The Need For Better Patient Stratificationmentioning
confidence: 99%
“…Trimodality therapy for esophageal and esophago-gastric cancer combining neoadjuvant chemo-and radiation-therapy in addition to surgery may also be superior to neoadjuvant chemotherapy alone in a selected patient population [8]. The CROSS trial [6] comparing neoadjuvant chemoradiotherapy plus surgery with surgery alone in patients with esophageal and esophago-gastric cancer showed a superior overall-survival of 49 vs. 24 months, hazard ratio 0.657, p = 0.003, and a pathological complete response rate of 29%, for patients with multi-modality treatment with no increase in surgical mortality (4% in surgery and trimodality groups, respectively).…”
Section: The Need For Better Patient Stratificationmentioning
confidence: 99%
“…The MAGIC study and the French FNCLCC/FFCD 9703 study were the first to show an overall survival benefit for perioperative chemotherapy in patients with lower esophageal, gastroesophageal junction (GEJ), and gastric adenocarcinoma. After these results, the CROSS study combined carboplatin/paclitaxel with 41.4 Gy radiation and demonstrated a 14% increase in 5‐year overall survival for patients with esophageal cancer (both squamous cell carcinoma and adenocarcinoma) treated with neoadjuvant chemoradiotherapy followed by surgery compared with surgery alone . However, the recently presented phase III FLOT 4 trial has shown that the FLOT regimen (docetaxel, oxaliplatin, leucovorin, and 5‐fluorouracil (5‐FU)) improves the outcome of patients with esophageal adenocarcinoma and locoregional disease as compared with the ECF/ECX triplet (epirubicin, cisplatin, and 5‐FU or capecitabine) .…”
Section: Perioperative Treatment For Locally Advanced Esophageal Cancermentioning
confidence: 99%
“…Currently, several randomized trials comparing perioperative chemotherapy and neoadjuvant chemoradiotherapy are being undertaken. The NeoAegis study compares CROSS versus MAGIC and the German ESOPEC study compares FLOT versus CROSS in patients with esophageal adenocarcinoma . The Chinese CMISG1701 study compares overall survival between neoadjuvant chemotherapy (cisplatin/paclitaxel) with neoadjuvant chemoradiotherapy (cisplatin/paclitaxel with 40 Gy radiation), both followed by esophagectomy for locally advanced resectable esophageal squamous cell carcinoma .…”
Section: Perioperative Treatment For Locally Advanced Esophageal Cancermentioning
confidence: 99%
“…Currently, there is no consensus regarding the management of patients with advanced local esophagogastric junction adenocarcinomas. If there is unanimity for Siewert I tumors regarding surgical technique, for Siewert II and III tumors there is still a matter of debate regarding surgical approach, operative risks that may occur and the postoperative complications (1).…”
Section: Introductionmentioning
confidence: 99%